Mobilizing luxury brands’ value added as investment in rangelands - Baker, Derek; Burkart, Stefan; Bravo, Aura; Dhehibi, Boubaker; Wane, Abdrahmane; Flintan, Fiona E. (2025)
A presentation contributing to the panel on the project STELARR (Sustainable Large-Scale Investments in Rangeland Restoration) at the International Rangelands Congress, June 2025, Adelaide, Australia.